The Influence Of Implementing The Strategic Policy In Creating Business Climate, Business Environment And Providing Support Facilities Towards Business Empowerment On Small Medium Craft Enterprises In Ambon Indonesia - Papilaya, Josef; Soisa, Thereesje Roza; Akib, Haedar (International Review of Management and Marketing, 2015)
This study aims at analyzing and explaining whether there was the influence of implementing the strategic policy in creating business climate, business environment and providing support facilities towards empowerment on small and medium enterprises as well as whether there is synchronously influence of implementing the strategic policy in creating business climate, business environment and providing support facilities for business empowerment on small and medium scale enterprises through a survey in the city of Ambon. The results show, that there is a positive and significant effect of implementing the strategic policy in creating business climate to empower small and medium enterprises. There is a positive and significant effect on the business environment toward the empowerment of small and medium enterprises, there is a positive and significant effect of providing support facilities toward the empowerment of small and medium enterprises, and there is a positive and significant simultaneously effect in business climate, business environment and support facilities for business towards the empowerment of small business in Ambon city. Empowerment programs are conducted to maintain a conducive business climate, including: 1). the innovation promotion, 2). enhancing human resources through training development; 3). providing financial support, 4). giving support to the marketing strategy, 5). opening the business partnership. While the supporting facilities granted to small and medium enterprises including: 1). giving the fishing boat for the Fishermen, 2). providing the workshop (machine shop service) facilities to small crafts business Enterprises, 3). establish vendors for small enterprises, 4). provide the area for street vendors, 5). provide tents for merchants culinary who work at night. Providing the assistance to encourage the business climate and create conducive business environment. Keywords: Business Climate; Business Environment; Support Business Facilities Empowerment JEL Classifications: M1